Gut microbiota partially mediates the effects of fine particulate matter on type 2 diabetes: Evidence from a population-based epidemiological study. (September 2019) - Liu, Tao; Chen, Xiaojiao; Xu, Yanjun; Wu, Wei; Tang, Wenli; Chen, Zihui; Ji, Guiyuan; Peng, Jiewen; Jiang, Qi; Xiao, Jianpeng; Li, Xing; Zeng, Weilin; et al.
Abstract: Background: Experimental studies have indicated that alterations in the gut microbiota might play a role in the pathway of diabetes induction resulting from particulate matter pollution with aerodynamic diameters < 2.5 μm (PM2.5 ). However, few human studies have examined such experimental findings. Here, we examine the mediating effects of gut microbial dysbiosis on the associations between PM2.5 and particulate matter pollution with aerodynamic diameters < 1 μm (PM1 ) on diabetes using the Guangdong Gut Microbiome Project (GGMP) dataset. Methods: A multistage cluster sampling method was employed to recruit adult participants from communities in Guangdong. Each participant was interviewed using a questionnaire, fasting blood and stool samples were collected, and the exposure to air pollutants was assessed using a spatiotemporal land-use regression model. The mediation analysis was conducted to estimate the associations among air pollutants, gut microbiota diversity and diabetes. Results: Both PM2.5 and PM1 were positively associated with the risks of impaired fasting glucose (IFG) or type 2 diabetes and negatively associated with alpha diversity indices of the gut microbiota. The mediation analyses indicated that the associations of PM2.5 and PM1 with the risk of type 2 diabetes were partially mediated by the decrease in gut microbiota diversity. Moreover, we found that 79 (PM2.5 on IFG), 84 (PM2.5 on type 2 diabetes), 83 (PM1 on IFG) and 89 (PM1 on type 2 diabetes) bacterial taxa could partially mediate the associations of PM2.5 and PM1 with IFG and type 2 diabetes, respectively. The relative abundance of most Firmicutes, Proteobacteria and Verrucomicrobia bacteria were negatively associated with particulate matter (PM) concentrations and the risks of diabetes. Conclusions: Long-term exposure to PM may increase the risk of diabetes, and alterations in the gut microbiota partially explained these associations. Graphical abstract: Unlabelled Image Highlights: Long-term exposure to PM may increase the risks of IFG and T2DM, and decrease the diversity of gut microbiota. The alternations of gut microbiota diversity could partially mediate the associations of PM with diabetes risk. Bacterial taxa could partially mediate the effects of PM2·5 and PM1 on IFG and T2DM.